Sleep quality and its relationship with mental well-being and work performance among nurses: a cross-sectional study - Norfidah Mohamad; Zamzaliza Abdul Mulud; Nurain Aqila Mohd Daud; Nurhidayah Abdul Halim; Noraini Hashim (PAGEPress Publications, 2024)
Poor sleep quality among nurses is a major concern for the healthcare system. It might impair the nurses' capacity to carry out their duties, endangering the patients' health and safety. The objectives of this study were to identify the levels of sleep quality, mental well-being, and work performance, and the relationship between these variables and work performance. A cross-sectional study was conducted among 143 nurses from teaching hospitals. A self-administered questionnaire consisting of the Pittsburgh Sleep Quality Index, the Warwick-Edinburgh Mental Well-being Scale, and the Individual Work Performance Questionnaire was used to measure sleep quality, mental well-being, and work performance, respectively. The findings indicated that 77.6% of nurses had poor sleep quality, and 90.2% had poor mental well-being. A p-value of 0.05 indicated a relationship between sleep and contextual performance, whereas p>0.05 indicated no relationship between mental health and sleep quality. Age and educational attainment were related to work performance, but only gender was associated with mental health (p=0.05). In conclusion, the study outcomes emphasized the critical importance of addressing poor sleep quality and mental well-being among nurses to optimize their contextual performance. The relationship between demographic factors and professional outcomes further underscored the complexity of factors influencing the well-being and performance of nurses, requiring tailored interventions for comprehensive improvement within this area.